Correlation Between TRAb and Early Onset Hypothyroidism After 131I Treatment for Gravesʼ Disease - Song, Qi; Fang, Zhouyu; Wang, Shurong; Liu, Zhihua; Xiao, Wenjin; Zong, Haijun; Xie, Ying (Hormone and Metabolic Research, 2024)
The aim of the study was to explore the clinical features related to early hypothyroidism and the relationship between the changes of thyrotropin receptor antibodies (TRAb) and early hypothyroidism in the course of 131I treatment for Graves’ disease. This study was a retrospective observation, including 226 patients who received the first 131I treatment. The general information and laboratory tests were collected before and after 131I treatment, and the laboratory data affecting the difference in disease outcome were analyzed. According to the changes of antibodies in the third month, whether the changes of antibodies were involved in the occurrence of early-onset hypothyroidism was analyzed. Early onset hypothyroidism occurred in 165 of 226 patients, and the results showed that the incidence of early hypothyroidism was higher in patients with low baseline TRAb level (p=0.03) and increased TRAb after treatment (p=0.007). Both baseline TRAb levels (p<0.001) and the 24-hour iodine uptake rate (p=0.004) are significant factors influencing the changes in TRAb. The likelihood of a rise in TRAb was higher when the baseline TRAb was less than 18.55 U/l and the 24-hour iodine uptake level exceeded 63.61%. Low baseline and elevated post-treatment levels of TRAb were significantly associated with early-onset hypothyroidism after 131I treatment. Monitoring this index during RAI treatment is helpful in identifying early-onset hypothyroidism and mastering the clinical outcome and prognosis of Graves’ disease.
Keywords: early onset hypothyroidism; 131I treatment; thyrotropin receptor antibody; Gravesʼ disease; retrospective observation